“Everything else is going to be ok if your spiritual wellness is well”. A qualitative exploration of wellness amongst secondary school students in Fiji - Latileta Odrovakavula (Taylor & Francis Group, 2021)
Purpose Adolescent wellness over the years has been a major public health concern. The adolescent period is stated to be a critical phase as developments occur in all areas of the individual. This study aims to explore secondary school students’ perceptions on knowledge of wellness, influences of wellness, prioritization of wellness dimensions and ideal adolescent wellness programmes in Fiji. Method This study qualitatively investigates adolescents in four purposively selected schools in Suva, Fiji. 31 students who enrolled into years 11 to 13 in the selected schools were interviewed in-depthly using a semi-structured, open-ended questionnaire. Data was transcribed and classified into categories, sub-themes and major themes. Results Participants’ responses indicated wellness perceived as multidimensional with no regard to dimensional balance. Family, peers and school support, social media, nutrition and physical activities are factors perceived to influence wellness. The availability of school counsellors, facilitation of effective school health programmes, and incorporation of wellness into the school curriculum were perceived as ideal ways to increase adolescent wellness. Conclusions This study provides important research findings of adolescent wellness for Fiji’s health sector, its policymakers and programme developers. Further studies are needed to understand the broad concept of wellness and its several dimensions.